Entanglement distribution - Zuppardo, Margherita (2017)
The main focus of this thesis is quantum entanglement and, more specifically, pro- tocols that allow its distribution between distant places. In the last decades, with the rise of attention on quantum technologies, entangle- ment is mostly seen as a resource, that could be exchanged, measured, and ideally stored and used when convenient. However, entanglement is not as stable and cheap as the classical resources. One reason for this is that entanglement between two quantum systems is easily disrupted by the interaction with the environment that surrounds them. The presence of noise is even more significant when we wish to entangle two systems that are very far away, a task that is essential for quantum communication technologies. In this case, what can disrupt the entanglement is not only the noise that the particles experience locally, but also the noise in the quantum channel during the communication process, which can be significant over long distances. For this reason, it is important to design distribution protocols that work well in such conditions. In 2003, Cubitt et al. showed the existence of a very curious class of protocols, often called entanglement distribution with separable states (EDSS). They proved that a non-entangled (separable) carrier can be used to increase, or even gener- ate entanglement between two already distant parties. From this, some questions arise. First, what limits or allows an entanglement distribution protocol, if not the entanglement that is sent. Quantum discord was shown to be a necessary, but not sufficient, resource for entanglement distribution. Another natural question is whether these protocols can beat others, for technological purposes, especially in noisy conditions. I will describe some work I have done in an attempt to partially 9 address both of these questions. After introducing various tools and concepts that are useful to understand this topic (chapter 1) and motivate the necessity of entanglement distribution in quantum communication (chapter 2), I will describe a proof-of-principle experiment demon- strating EDSS schemes (chapter 3). Later (chapter 4), I will introduce a more general classification of distribution protocols (excessive or non-excessive protocols), based on whether the entanglement gain is larger than the one that is communicated, describing specific examples and general properties of such protocols. I will then partially address the problem regarding the robustness to the noise of communica- tion protocols (chapter 5). Finally, in chapter 6, I will describe how entanglement of a bipartite state can grow with a quantum measurement with unknown results. I discuss the properties of the measurement and of the initial state that make this process effective.